Storia di una comune agricola. Il ritorno alla terra come scelta politica ed esistenziale - Petrioli, Valentina (Scienze del Territorio, 2014)
The paper reports the experience of a farming commune founded in the late seventies in Umbria. After a brief historical reconstruction of the events leading to the birth and development of the commune, the analysis focuses on the social and economic background in which it was born. It focuses on the relationship that young communards have with the old local peasants, custodians of the rural culture of their sharecropping families; but also on their correlation with a new generation of peasants coming, like them, from the excitement of student protests that characterized city life at the time. After tracing a regional network of solidarity, which continues to the present day, the article closes on the individual and collective choices that a community takes to stay out of the consumer society by putting into practice what Ivan Illich called subsistence economy.